Peace as a Minor, Grounded Utopia: On Prefigurative and Testimonial Pacifism. Issue 4 (December 2019) - Thaler, Mathias
Abstract : A common complaint about pacifism holds that it is utopian, in a pejorative sense. The worry can take various forms and directions, but when it is couched in terms of just war theory it usually includes accusations of pacifism's immorality, inconsistency and impracticality. Contemporary defenders of pacifism have responded to this complaint by delineating a highly sophisticated, empirically informed account of pacifism that foregrounds its real-world effectiveness. This article takes a different route to vindicating pacifism via a more nuanced picture of what is specifically utopian about it. I propose that peace, in at least some of its guises, can be described as a minor, grounded utopia; it is a desire for an alternative future without war and violence, whose pursuit blurs the boundaries between thought and action. Reconstructing both prefiguration and testimony as practical modes of this kind of pacifism, I maintain that minor, grounded utopias are sites rife with conflict and contestation.